PERANAN SULTAN DALAM PERKEMBANGAN ISLAM DI NEGERI PAHANG - Rosele, Muhammad Ikhlas; Abd Rahim, Rahimin Affandi; Wan Ali, Wan Zailan Kamaruddin (Jurnal Pengajian Melayu (JOMAS), 2018)
Islam in Malaysia has a unique historical background. The question on how Islam came to Malay Archipelago is still debated and has yet to be explained definitively. Throughout history, many entities have contributed in terms of how Islam came to be accepted, spread and practiced, and unltimately attained official status in Malaysia. The role and contribution of royal institutions in spreading and protecting Islam is significant and well documented. This article analyses the role of the Pahang sultanate in spreading Islam in that state. It reviews that role from different viewpoints, such as relations between the Sultan and Islamic scholars (ulama), the Hukum Kanun Pahang (Canonical Law of Pahang), the role of Sultan as defined in the state constitution, and his contributions to the maintenance of Islam in the Malay Archipelago. Keywords: The Sultanate of Pahang, the spreading of Islam, ulama’, the Law of Pahang.